2009
DOI: 10.1182/blood-2008-08-172767
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of monocyte-derived inflammatory cytokines by IL-25 occurs via p38 Map kinase–dependent induction of Socs-3

Abstract: Introduction (also known as IL-17E) is a recently described member of the IL-17 cytokine gene family. IL-25 is made by several cell types, including T lymphocytes, mast cells, eosinophils, and basophils. 1,2 IL-25 can also be produced by lung epithelial cells and alveolar macrophages on allergen stimulation. 3,4 Unlike other members of the IL-17 family, IL-25 facilitates pathogenic Th2 cell responses. Studies in mice have shown that transgenic expression of IL-25, or systemic administration of recombinant cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
46
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 33 publications
11
46
0
1
Order By: Relevance
“…1,5 However, IL-25 also plays a critical role in suppressing intestinal chronic inflammation, regulating adipose tissue inflammation and protecting against LPS-induced lethal endotoxemia. 3,25,26 We have demonstrated that IL-25 attenuated renal injury in AN, a model of CKD, whereas the potential role of IL-25 in acute kidney disease is unclear. AKI induced by IRI is associated with an acute reduction of blood flow that produces hypoxiainduced vascular and tubular dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…1,5 However, IL-25 also plays a critical role in suppressing intestinal chronic inflammation, regulating adipose tissue inflammation and protecting against LPS-induced lethal endotoxemia. 3,25,26 We have demonstrated that IL-25 attenuated renal injury in AN, a model of CKD, whereas the potential role of IL-25 in acute kidney disease is unclear. AKI induced by IRI is associated with an acute reduction of blood flow that produces hypoxiainduced vascular and tubular dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…There are several reports that have implicated p38 MAPK in playing a major role in induction of SOCS3 (32,(65)(66)(67). Because earlier we found that PPE18 interacts with the LRR 11-15 domain of TLR2 and leads to an early and sustained activation of p38 MAPK, which was critical for IL-10 induction (24), it was reasonable to expect that PPE18 increased the SOCS3 levels in THP-1 macrophages via activation of p38 MAPK.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have implicated a prominent role of p38 MAPK signaling in SOCS3 induction (32,(65)(66)(67). In our previous study, we found that PPE18 induces early activation of p38 MAPK, which is in turn necessary for the IL-10 induction via TLR2 (24).…”
Section: Ppe18 Induces Expression Of Socs3 and Its Phosphorylation Atmentioning
confidence: 96%
“…IL-25R also is expressed on human eosinophils, monocytes, airways smooth muscle cells, and fibroblasts (16)(17)(18)(19), raising the possibility that IL-25 also may be involved in causing structural changes in the airways that characterize asthma. However, its possible role in angiogenesis has never been explored.…”
Section: Il-25 (Il-17ementioning
confidence: 99%